Metamorphosis a guide to the World Wide Web & electronic commerce - McKeown, Patrick G; Watson, Richard Thomas (J. Wiley, 1996)
Provides a thorough overview of the world of electronic commerce, including background on client/server networks, the internet, browsers, accessing the web, and other resources that have an impact on businesses and organizations. It will aid organizations in making the transformation from old way of doing business and interacting with customers, suppliers, employees, etc., to new ways utilizing the web and internet.